1996
DOI: 10.1159/000188944
|View full text |Cite
|
Sign up to set email alerts
|

Patch-Clamp Study on T-Lymphocyte Potassium Conductance in Patients with Chronic Renal Failure

Abstract: Using the patch-clamp technique, we studied the differences in whole-cell potassium conductance (gκ+) in T lymphocytes (TL) from three groups of patients suffering from renal failure: not dialyzed patients, dialyzed patients, and dialyzed patients treated with human recombinant erythropoietin (rHu-EPO). The difference in gκ+ values in the group of not dialyzed patients in comparison with controls was not significant (p > 0.05). In the group of dialyzed patients, after roughly 6 years of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A patch-clamp study found an electrophysiological relevance in this context, demonstrating increased conductance of voltage-dependent K ? channels in lymphocytes of these patients [87]. The study also revealed that the activity of the channels was deeply associated with the severity of CRF.…”
Section: Effects Of Ccbs On Kv13-channel Currents and Whole-cell Memmentioning
confidence: 64%
“…A patch-clamp study found an electrophysiological relevance in this context, demonstrating increased conductance of voltage-dependent K ? channels in lymphocytes of these patients [87]. The study also revealed that the activity of the channels was deeply associated with the severity of CRF.…”
Section: Effects Of Ccbs On Kv13-channel Currents and Whole-cell Memmentioning
confidence: 64%
“…Peripheral lymphocytes are activated and the serum cytokine levels are known to be elevated in patients with end-stage renal disease [ 12 14 ]. Based on a previous patch-clamp study [ 42 ], the conductance of voltage-dependent K + -channels in lymphocytes was increased in such patients and the activity of the channels was strongly associated with the severity of renal dysfunction. In experimental animal models of renal diseases, such as renal allograft rejection [ 10 ] and glomerulonephritis [ 9 ], immunosuppression by the blockade of lymphocyte Kv1.3-channels actually prevented or ameliorated the progression of the diseases.…”
Section: Pathological Roles Of Lymphocyte Kv13-channels In Renal mentioning
confidence: 99%